Estudos sobre as instituições participativas: o debate sobre sua efetividade - Romão, Wagner de Melo [UNESP] (2013)
The main purpose of this article is to introduce the debate on the effectiveness of the participatory institutions in Brazil. At first, it will bring the very early debate about participatory democracy and deliberative democracy. Afterwards, the article will show how international literature impacts studies on the democratic transition in Brazil, trying to delineate the borders, limitations and advances of Brazilian literature about the theme. In the last part, the main topics of debate on the effectiveness of participatory institutions - methods and instruments of evaluation - will be pointed out